Tumbangnya rezim Soeharto - Soeharto, Haji, 1943- (Surabaya : Bina Ilmu, 1998)
Events relating to the resignation of former President Soeharto.
Keywords: Soeharto, -- 1921-2008 -- Resignation from office; Presidents -- Term of office -- Indonesia; Indonesia -- Politics and government -- 1966-